A D-3He fusion reactor for the mitigation of global warming - E. Mazzucato (Fundamental Plasma Physics, 2023)
Since a fusion reactor using the Deuterium-Tritium fuel cycle cannot be a source of clean energy because of the deleterious effects of energetic neutrons carrying 80% of the energy output, and it is very doubtful that it will be able to achieve Tritium self-sufficiency because of an extremely problematic and still unproven breeding procedure, this paper proposes a new reactor scheme capable of confining hot and dense plasmas using the Deuterium – Helium-3 fuel cycle. Such a reactor must be considered a source of clean energy because of its very low level of neutrons production, and its fuel is available in large quantity since we can get the needed Deuterium from seawater and likewise Helium-3 from the moon, as it was found from the samples of lunar soil brought back by the astronauts of the Apollo Mission. The proposed reactor consists of two 100 m long cylindrical plasmas, connected by semicircular sections to form a racetrack configuration. It should be capable of producing from 16 to 20 GW of fusion power when operating with an electron density of 3 × 1020 m−3, a magnetic field of 10 T and average temperatures from 40 to 45 keV. Out of this power, up to 10 GW will be used for replacing the loss of electron energy from bremsstrahlung radiation, with a consequent reduction in the reactor power output. However, such a loss could be mitigated by a partial recovery of the energy plasma radiation.